Penggunaan WordWall sebagai Game Edukasi untuk Meningkatkan Keterampilan Abad 21 di Sekolah Dasar - Siti Mumtazah; Salmaini Safitri Syam; Nur Azmi Alwi (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
The development of information technology encourages innovation in learning methods, one of which is through digital educational games. This study aims to assess the effectiveness of Wordwall educational game-based learning media in improving elementary school students' 21st century skills, such as critical thinking, creativity, collaboration, and communication. The method used is a literature study by analyzing various scientific sources and relevant research. The results showed that Wordwall is able to increase students' motivation and interest in learning through interactive features and a variety of games that are easily adapted to the subject matter. Obstacles faced include limited access to technology and teacher readiness, which can be overcome with intensive training and provision of adequate facilities. Therefore, Wordwall is proven to be effective and relevant as a learning media that supports the 21st century learning process in elementary schools. It is recommended that the utilization of Wordwall be optimized through continuous training for teachers and provision of adequate technological facilities to improve the quality of learning.